Real-time frequency stabilization of standalone PV system with SMC - Gnanam, Nisha; Kamaraj, Jamuna (International Journal of Innovative Research and Scientific Studies, 2023)
This paper aims to obtain suitable control for the Standalone Photo Voltaic (SAPV) system to meet consumer demands in weather conditions. A SAPV system is developed with a solar array with Maximum Power Point Tracking (MPPT), a Boost converter, and an inverter. This system uses controllers for maximum power output tracking, constant DC output of the Boost converter, and constant output voltage and frequency with Pulse Width Modulation (PWM) control mode. MPPT, boost converter, and inverter controller parameters are designed and tuned, respectively. Proportional gain (Kp) and Integral gain (Ki) values and the Sliding Mode Method (SMC) tune the controller parameters. The innovative aspect of this work is to propose a standalone PV system with controllers based only on the sliding mode control approach. Moreover, the current controller provides an output current of high quality with a THD of 1.6 %. Effectiveness and robustness of the proposed scheme modeled and simulated under OPAL-RT real-time Software in Loop (SIL) platform with MATLAB Simulink under fast variations of irradiance and temperature. Various analyses have been carried out for examining the proposed Sliding Mode Controller-based standalone photovoltaic system.